Contaminant Characteristics and Influencing Factors of Heavy Metals in Seawater and Sediments in a Typical Mariculture Bay in South China - Lao, Qibin; Cai, Shangjun; Huang, Peng; Chen, Fajin; Su, Qizhong; Lei, Xuetie; Zhou, Xin; Chen, Chunqing; Zhu, Qingmei; Lu, Xuan; Liu, Guoqiang (Frontiers in Marine Science, 2022)
Heavy metal pollution in the mariculture areas is of considerable attention due to its potential ecological effects and public concern for seafood safety. A better understanding of the current contamination status and historical trend of heavy metals in the ecosystems of mariculture areas has an important implication for the sustainable development of marine ecosystems and for public health concerns. To assess the impact of human activities on heavy metal pollution in the mariculture area, seven metals (Cu, Pb, Zn, Cd, Hg, As, and Cr) and the environmental parameters were seasonally investigated in the surface seawater and sediments in Qinzhou Bay, a typical mariculture bay in South China. Seasonal variations in the concentration of heavy metals were found in both seawater and sediment, which are mainly influenced by seasonal hydrological change, biological activity, and human influence. The concentration of heavy metals in the seawater was at a relatively higher level than that of other mariculture areas in China, while a lower level was found in the sediment. The concentration of Cu increased in both seawater and sediment for the past decades (by nearly 2 times), which is mainly influenced by the mariculture and shipping activities. The concentration of Hg decreased significantly in the seawater for the past 40 years (decreased by 13 times) due to the decrease in production and usage of Hg. However, the concentrations of Pb, Zn, and Cd in seawater showed an increasing trend in the mariculture bay, while the concentrations of Pb, Zn, As, and Cr decreased in the sediment over the past decades. The decrease in pH value (decreasing by 4.7% for the past 20 years) was responsible for the different trend of those metals between seawater and sediment because the decrease in pH could re-release metals from sediments into the water column. Hg and As are the main ecological risk factors in the mariculture bay. This study suggests that environmental changes, such as ocean acidification, affect the distribution of metals in seawater and sediments, which we should be more vigilant and concerned about under the global climate change.